2004
DOI: 10.1007/s00049-003-0260-2
|View full text |Cite
|
Sign up to set email alerts
|

New repellent semiochemicals for three species of Dendroctonus (Coleoptera: Scolytidae)

Abstract: Nine compounds identified from captured volatiles of the Douglas-fir beetle, Dendroctonus pseudotsugae, the mountain pine beetle, D. ponderosae, and the spruce beetle, D. rufipennis, that elicited antennal responses in males and females of one or more of these species were tested in the field to determine behavioural activity. 1-Octen-3-ol, found in the volatiles of females of all three species decreased the response of male and female coastal and male interior D. pseudotsugae and both sexes of D. ponderosae t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 55 publications
(78 reference statements)
2
42
0
Order By: Relevance
“…If catch in the challenged trap is significantly lower than the control, the test bait is concluded to be inhibitory; if catch is significantly higher than the control, the test bait is concluded to be a synergist or attraction enhancer (Payne et al 1978a;Bedard et al 1980;Bakke 1981;Pureswaran and Borden 2004;Sullivan 2005). Our data demonstrate how such attractant-challenge tests might generate misleading or inconsistent conclusions regarding the activity of a compound.…”
Section: Discussionmentioning
confidence: 99%
“…If catch in the challenged trap is significantly lower than the control, the test bait is concluded to be inhibitory; if catch is significantly higher than the control, the test bait is concluded to be a synergist or attraction enhancer (Payne et al 1978a;Bedard et al 1980;Bakke 1981;Pureswaran and Borden 2004;Sullivan 2005). Our data demonstrate how such attractant-challenge tests might generate misleading or inconsistent conclusions regarding the activity of a compound.…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds inhibit responses of flying beetles to traps baited with frontalin and α-pinene (Sullivan, 2005;Sullivan et al, 2007a), and 2-phenylethanol reduced responses of beetles to attractant in an ambulatory olfactometer (Brand et al, 1977). These compounds have been detected in other species of Dendroctonus and Ips (Kohnle et al, 1987;Pureswaran and Borden, 2004;Pureswaran et al, 2000;Renwick et al, 1976b;Zhang et al, 2007), and have demonstrated behavioural activity with some (Erbilgin et al, 2007a(Erbilgin et al, , 2008Pureswaran et al, 2000). It was shown in Ips pini that 2-phenylethanol is generated from the amino acid phenylalanine, and both this compound and acetophenone appear to be amino acid derivatives (Gries et al, 1990b;Seybold and Vanderwel, 2003).…”
Section: Non-monoterpene Aromaticsmentioning
confidence: 97%
“…Other reports showed similar disruption by alcohols, with the two most effective being (Z)-3-hexen-1-ol and (E)-2-hexen-1-ol [25]. 1-Octen-3-ol was not only identified in the bark volatiles of European birch and aspen [30,31] but also identified in females of D. ponderosae, D. rufipennis, and D. pseudotsugae [14]. Further field tests found that 1-octen-3-ol was repellent to all three Dendroctonus spp.…”
Section: Discussionmentioning
confidence: 54%
“…Further field tests found that 1-octen-3-ol was repellent to all three Dendroctonus spp. (D. ponderosae, D. rufipennis, and D. pseudotsugae), and 1-octen-3-ol can be potentially be classified as an antiaggregation pheromone, or serve as a kairomone, indicating unacceptable hosts or non-hosts [14]. In development and implementing a semiochemical-based management program for D. valens, NHVs may have considerable potential for disrupting the beetle's ability to locate suitable hosts.…”
Section: Discussionmentioning
confidence: 99%